The Role of IPR in Plant Genetic Engineering - Bhattacharjee, Abhishek Rajesh; Das, Shreya; Aastha, Stuti (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
The role and status of Patent laws in the protection of plant species which have been genetically modified is currently uncertain in India. Discussions and debates regarding the same are rife and experts have different views regarding the whole aspect concerning economical and ethical considerations. Genetically engineered plants and modified crop plants are of significant economic value. In India, they face critical challenges, for instance, the requirement of dependable public policies and vigorous frameworks for regulatory control. This becomes much more vital since India desires to be an economic superpower primarily based on innovation. It is very important for a person from the legal field, especially those interested in the field of IPR, to have clarity regarding the protection of genetically modified plants. This humble attempt at a research paper seeks to clarify the same and discusses the various aspects on which one should think while concluding their views on the topic.